Methylenetetrahydrofolate Dehydrogenase 1 Polymorphisms Modify the Associations of Plasma Glycine and Serine With Risk of Acute Myocardial Infarction in Patients With Stable Angina Pectoris in WENBIT (Western Norway B Vitamin Intervention Trial). (December 2016) - Ding, Yunpeng; Pedersen, Eva R.; Svingen, Gard F.T.; Helgeland, Øyvind; Gregory, Jesse F.; Løland, Kjetil H.; Meyer, Klaus; Tell, Grethe S.; Ueland, Per M.; Nygård, Ottar K.
Abstract : Background—: Serine and glycine interconversion and methylenetetrahydrofolate dehydrogenase 1 (MTHFD1)–mediated 1-carbon transfer are the major sources of methyl groups for 1-carbon metabolism. Recently, plasma glycine and a common polymorphism in MTHFD1 have been associated with risk of acute myocardial infarction (AMI). It is, therefore, of interest to explore if these 2 pathways interact in relation to AMI. Methods and Results—: A total of 2571 participants in the WENBIT (Western Norway B Vitamin Intervention Trial) undergoing coronary angiography for stable angina pectoris were studied. Associations of plasma serine and glycine concentrations with risk of AMI across 2 common and functional MTHFD1 polymorphisms ( rs2236225 and rs1076991 ) were explored in Cox regression models. During a median follow-up of 4.7 years, 212 patients (8.2%) experienced an AMI. In age- and sex-adjusted analyses, plasma glycine ( P <0.01), but not serine ( P =0.52), showed an overall association with AMI. However, interactions of MTHFD1 rs2236225 polymorphism with both plasma serine and glycine were observed ( P interaction =0.03 for both). Low plasma serine and glycine were associated with an increased risk of AMI among patients carrying the rs2236225 minor A allele. Similarly, low plasma glycine showed stronger risk relationship with AMI in the rs1076991 CC genotype carriers but weaker associations in patients carrying the minor T allele ( P interaction =0.02). Conclusions—: Our results showed that 2 common and functional polymorphisms in the MTHFD1 gene modulate the risk associations of plasma serine and glycine with AMI. These findings emphasize the possible role of the MTHFD1 in regulating serine and glycine metabolism in relation to atherosclerotic complications. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique Identifier: NCT00354081.